(untitled) (Politeja, 2020)
Memory and Objects. About the Autobiographical Narratives Written by Lydia Flem and Marcin Wicha The aim of paper is to discover traces of the deceased and recreate bonds between a human and an object (objects). In the narrative two autobiographies were analysed: Lydia Flem’s ‘How I emptied my parents’ house’ (‘Comment j’ai vidé la maison de mes parents’) and Marcin Wicha’s ‘Items I didn’t throw away’ (‘Rzeczy, których nie wyrzuciłem’). Both authors mourn their mothers. According to the specific Jewish ‘idiom’ they run a post-cmemorial thread related to their mothers’ origins and historical implications (post-memory is understood, after Marianne Hirsch, as a specific kind of transfer of some traumatic experience).